2020
DOI: 10.34172/apb.2021.073
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of the Antibacterial Effect of Chitosan Nanoparticles Containing Ginger Extract Tailored by Central Composite Design

Abstract: The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A dynamic light scattering (DLS) experiment was employed to determine the size, zeta potential, and PDI (polydispersity index) of MET-loaded NPs (Zetasizer Nano ZS system, Malvern Instruments, Worcestershire, UK) [ 27 ]. The angle of detection was 90°, the temperature was 25°C, the concentration of the specimens was 20–400 kilo counts per second, and the intensity of diffraction was 100 kilo counts per second.…”
Section: Methodsmentioning
confidence: 99%
“…A dynamic light scattering (DLS) experiment was employed to determine the size, zeta potential, and PDI (polydispersity index) of MET-loaded NPs (Zetasizer Nano ZS system, Malvern Instruments, Worcestershire, UK) [ 27 ]. The angle of detection was 90°, the temperature was 25°C, the concentration of the specimens was 20–400 kilo counts per second, and the intensity of diffraction was 100 kilo counts per second.…”
Section: Methodsmentioning
confidence: 99%
“…Chitosan nanoparticles of permethrin were synthesised by ionic gelation method [4717]. The chitosan powder was dissolved in 1% (v/v) acetic acid solution followed by 15–20 min of constant stirring on a magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that nanoparticle-based delivery technologies improve the biological activity of herbal extracts as prebiotics 62 . For instance, by specifically encouraging the growth of advantageous gut bacteria, the encapsulating of ginger extract in chitosan nanoparticles improved its stability and increased its prebiotic effect 63 . Similar to this, resveratrol's solubility and stability were increased through its encapsulation in solid lipid nanoparticles, enabling targeted administration to the colon and regulation of the gut microbiota 64 .…”
Section: Nanoparticle-based Delivery Systemsmentioning
confidence: 99%